2009
DOI: 10.1111/j.1365-2567.2009.03097.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T‐cell immunity by leucocyte immunoglobulin‐like receptors: innate immune receptors for self on antigen‐presenting cells

Abstract: Summary Following recognition of microbial patterns, innate immune receptors provide a rapid innate response and trigger antigen‐presenting cell maturation to instruct adaptive immune responses. Here we discuss a family of innate immune receptors for self – the leucocyte immunoglobulin‐like receptors (LILRs). These LILRs exert powerful inhibitory effects on antigen‐presenting cell phenotype and subsequent T‐cell responses, and may act to constrain the effects of Toll‐like receptor signalling. Despite their bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 95 publications
(176 reference statements)
0
72
0
Order By: Relevance
“…Thus, LILRs with inhibitory and stimulatory activity can also influence the antigen-presenting properties of macrophages and dendritic cells and may thus play a role in T cell tolerance. The wide-ranging effects of LILR signaling on immune cell activity imply that these receptors are likely to play an important role in a range of clinical situations, including autoimmune diseases, infectious diseases, transplantation, and cancer [33,34]. Actually, it has been reported that triggering of LILRs through their interaction with self proteins can modulate the DC activation status, antigen-presenting functions, and the capacity to elicit T cell responses [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LILRs with inhibitory and stimulatory activity can also influence the antigen-presenting properties of macrophages and dendritic cells and may thus play a role in T cell tolerance. The wide-ranging effects of LILR signaling on immune cell activity imply that these receptors are likely to play an important role in a range of clinical situations, including autoimmune diseases, infectious diseases, transplantation, and cancer [33,34]. Actually, it has been reported that triggering of LILRs through their interaction with self proteins can modulate the DC activation status, antigen-presenting functions, and the capacity to elicit T cell responses [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that this receptor controls inflammatory responses and cytoxicity, limiting auto reactivity. 46 There is no information in the literature that helps to correlate Lilrb3 upregulation with the double-mutant phenotype.…”
Section: Characterization Of Each Dystrophic Strainmentioning
confidence: 99%
“…It is known that HLA-G mRNA transcription is up-regulated by hormones (i.e., progesterone) [48] and interferons (IFNs) [49]. Interleukin-10 up-regulates both HLA-G [50,51] and its receptors LILRB1 and LILRB2 [52]. Hypoxia induces the expression of all HLA-G transcripts in term CTBs [53]; epidermal growth factor (EGF), a trophoblast growth and syncytialization factor, enhances protein expression of HLA-G5 [41].…”
Section: Physiological Conditionsmentioning
confidence: 99%